Pengaruh Manajemen Laba, Strategi Bisnis, Dan Kepemilikan Manajerial Terhadap Financial Distress - Sawitri, Ria; Harahap, Aderina; Vitratin, -; Yuliana, -; Eliyana, Rahmi (Universitas Malahayati, 2025)
Financial distress refers to a condition in which a company experiences financial difficulties that, if not addressed promptly, can lead to bankruptcy. This condition allows stakeholders to assess the company from various perspectives, including through the analysis of financial statements. This study aimed to empirically examine the influence of earnings management, business strategy, and managerial ownership on financial distress. The research employed a quantitative method with an associative approach. Secondary data were collected from the official website of the Indonesia Stock Exchange (IDX). The sample consisted of 14 manufacturing companies in the technology subsector listed on the Indonesia Stock Exchange during 2019-2023. The study used panel data regression analysis, supported by EViews 12 software. The results proved that earnings management had a significant positive influence on financial distress. In contrast, business strategy and managerial ownership had no significant influence on financial distress.